Comparison of preoperative imaging and pathological findings for pancreatic head adenocarcinoma: A retrospective analysis by the Association Française de Chirurgie. Issue 24 (June 2017) - Gilabert, Marine; Boher, Jean-Marie; Raoul, Jean-Luc; Paye, François; Bachellier, Philippe; Turrini, Olivier; Delpero, Jean Robert
Abstract : Abstract: Initial imaging of pancreatic ductal adenocarcinoma is of crucial importance in the decision-making process. The aim of this study was to compare preoperative imaging, pathological data, and outcomes in a series of patients who underwent resection for pancreatic head cancer. From January 2004 to December 2009, data were collected by the Association Française de Chirurgie on 1044 patients who received first-line R0 resection of pancreatic head cancer. On imaging (computed tomography scan 97%, echoendoscopic ultrasound 61.3%, magnetic resonance imaging 46.5%), arterial, venous, or lymph node invasion was suspected in 20, 161, and 197 patients, respectively; arterial, venous, or lymph node invasion was observed histologically in 11, 116, and 736 cases, respectively. In the patients for whom both imaging and pathological data were available, the concordance, sensitivity, specificity, positive predictive value, and negative predictive value were as follows: 97.5%, 27.3%, 98%, 20%, and 99%, for arterial invasion; 86.5%, 54%, 91%, 47.8%, and 93.2%, for venous invasion; and 38%, 21%, 86%, 78%, and 41%, respectively, for lymph node invasion. Imaging of arterial invasion had no prognostic value, while histological evidence of invasion was associated with a poor prognosis. Venous and lymph node invasion, as demonstrated by imaging and by pathological analysis, had an adverse prognostic value. Imaging gives a fair positive predictive value for venous or arterial invasion; venous invasion on imaging and histology was associated with a poor prognosis; arterial invasion on imaging does not have any significant prognostic value.